2022
DOI: 10.32735/s0718-6568/2022-n61-1667
|View full text |Cite
|
Sign up to set email alerts
|

De la revuelta al encierro: organización, resistencia y solidaridad feminista en Chile en tiempos de pandemia

Abstract: Este artículo tiene como objetivo central reflexionar sobre ¿cómo y en qué medida la pandemia ha afectado y modificado las formas de activismo feminista en Chile? ¿Qué impactos ha tenido el encierro en las formas de organizarse, en la capacidad de convocatoria y presión social? ¿Cuál ha sido la particularidad del caso chileno, considerando la pandemia en el intermedio de la revuelta social y el proceso constituyente? ¿Cuáles han sido los esfuerzos desplegados para mantenerse activas? Con base en los resultados… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Early results revealed that behind this fear-based passivity, many local initiatives were developed precisely as a survival mechanism, a way for marginalised communities to self-sustain in the context of a perceived abandonment by health authorities and the State. Unsurprisingly, the main form of action developed at the grassroots level where the 'ollas comunes', cooperative cooking of meals for people who, due to the pandemic, couldn't afford food -provided a strategy of resistance and solidarity that had only been seen with this intensity in the 1980s, amid dictatorship and a deep economic crisis (Espinoza, 2020).…”
Section: Social Mobilisation and Community Participation In South Ame...mentioning
confidence: 99%
“…Early results revealed that behind this fear-based passivity, many local initiatives were developed precisely as a survival mechanism, a way for marginalised communities to self-sustain in the context of a perceived abandonment by health authorities and the State. Unsurprisingly, the main form of action developed at the grassroots level where the 'ollas comunes', cooperative cooking of meals for people who, due to the pandemic, couldn't afford food -provided a strategy of resistance and solidarity that had only been seen with this intensity in the 1980s, amid dictatorship and a deep economic crisis (Espinoza, 2020).…”
Section: Social Mobilisation and Community Participation In South Ame...mentioning
confidence: 99%